2015
DOI: 10.1051/0004-6361/201526057
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous X-ray and optical spectroscopy of the Oef supergiantλCephei

Abstract: Context. Probing the structures of stellar winds is of prime importance for the understanding of massive stars. Based on their optical spectral morphology and variability, it has been suggested that the stars in the Oef class feature large-scale structures in their wind. Aims. High-resolution X-ray spectroscopy and time-series of X-ray observations of presumably single O-type stars can help us understand the physics of their stellar winds. Methods. We have collected XMM-Newton observations and coordinated opti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 91 publications
(163 reference statements)
12
46
0
Order By: Relevance
“…In terms of a stationary description, a simple model (e.g., Hillier et al 1993;Cassinelli et al 1994) assumes randomly distributed shocks above a minimum radius, R min ≈ 1.5 R * . This is consistent with X-ray line diagnostics ( e.g., Leutenegger et al 2013b; see also Rauw et al 2015) in which the hot shocked gas (with temperatures of a few million Kelvin and a volume filling factor on the order of 10 −3 to a few 10 −2 ) is collisionally ionized/excited and emits X-ray/EUV photons due to spontaneous decay, radiative recombinations, and bremsstrahlung. The ambient, cool wind then reabsorbs part of the emission, mostly via K-shell processes.…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…In terms of a stationary description, a simple model (e.g., Hillier et al 1993;Cassinelli et al 1994) assumes randomly distributed shocks above a minimum radius, R min ≈ 1.5 R * . This is consistent with X-ray line diagnostics ( e.g., Leutenegger et al 2013b; see also Rauw et al 2015) in which the hot shocked gas (with temperatures of a few million Kelvin and a volume filling factor on the order of 10 −3 to a few 10 −2 ) is collisionally ionized/excited and emits X-ray/EUV photons due to spontaneous decay, radiative recombinations, and bremsstrahlung. The ambient, cool wind then reabsorbs part of the emission, mostly via K-shell processes.…”
Section: Introductionsupporting
confidence: 87%
“…Hillier et al (1993) analyzed the sensitivity to R min , pointing to indistinguishable X-ray flux differences when the onset is varied between 1.5 and 2 R * . Recent analyses of X-ray line emission from hot star winds also point to values around 1.5 R * (e.g., Leutenegger et al 2006;Oskinova et al 2006;Hervé et al 2013;Cohen et al 2014b), although Rauw et al (2015) derived a value of 1.2 R * for the wind of λ Cep.…”
Section: X-ray Emissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sundqvist et al (2011) argued that the photospheric contribution of the He ii blend with Hα is negligible. Rauw et al (2015) found the dominant frequency to be ν 2 (our adopted rotation frequency) in this line; it is most likely also present in our data two months later, but this is difficult to confirm as ν 2 is close to the lower frequency limit (set by the temporal coverage) in our Fourier analysis. Marchenko et al (1998), which is remarkably present in 2012.…”
Section: Power Spectramentioning
confidence: 50%
“…With the fourfold exposure time available now, the new combined RGS spectrum is of significantly better quality, and we can use it to further characterize the soft X-ray emission. Unfortunately, a detailed modelling such as done for ζ Pup (Hervé et al 2013) or λ Cep (Rauw et al 2015b) cannot be done in this case. Even though the emission in the soft band is probably only very little affected by the wind interaction, 9 Sgr hosts two stars, both of which are likely to contribute to the X-ray emission.…”
Section: High-resolution X-ray Spectroscopymentioning
confidence: 99%